Testing Navigation in Real Space: Contributions to Understanding the Physiology and Pathology of Human Navigation Control - Schöberl, Florian; Zwergal, Andreas; Brandt, Thomas (Frontiers in Neural Circuits, 2020)
Successful navigation relies on the flexible and appropriate use of metric representations of space or topological knowledge of the environment. Spatial dimensions (2D versus 3D), spatial scales (vista-scale versus large-scale environments) and the abundance of visual landmarks critically affect navigation performance and behaviour in healthy human subjects. Virtual reality based navigation paradigms in stationary position have given insight into the major navigational strategies, namely egocentric (body-centered) and allocentric (world-centered), and the cerebral control of navigation. However, virtual reality approaches are biased towards optic flow and visual landmark processing. This major limitation can be overcome to some extent by increasingly immersive and realistic virtual reality set-ups (including large screen projections, eye tracking and use of head-mounted camera systems). However, the highly immersive virtual reality settings are difficult to apply particularly to older subjects and patients with neurological disorders because of cybersickness and difficulties with learning and conducting the tasks. Therefore, a need for the development of novel spatial tasks in real space exists, which allow synchronous analysis of navigational behaviour, strategy, visual explorations and navigation-induced brain activation patterns. This review summarizes recent findings from real space navigation studies in healthy subjects and patients with different cognitive and sensory neurological disorders. Advantages and limitations of real space navigation testing and different virtual reality based navigation paradigms are discussed in view of potential future applications in clinical neurology.